The Use of Wearable Devices for Blood Glucose Monitoring in Diabetes Mellitus Patients: A Comprehensive Review of Technology, Clinical Impact, and Future Prospects (Proceedings OPTIMAL, 2025)
Accurate and continuous blood glucose (glucose) monitoring is a crucial cornerstone of effective diabetes management. Wearable devices have emerged as transformative technology, promising significant improvements in glucose monitoring compared to conventional (fingerstick) methods. This comprehensive review explores the landscape of wearable technology for glucose monitoring, analyzes its clinical impact, and outlines future prospects. We conducted a systematic literature search on leading scientific databases (PubMed, IEEE Xplore, Scopus) for recent studies (2019-2025). This review categorizes key technologies, including electrochemical enzymatic sensor-based Continuous Glucose Monitoring (CGM), optical sensors (NIR/MIR spectroscopy, Raman, fluorescence), and multimodal approaches integrated into patches, smartwatches, or textile-based devices. Analysis of the clinical impact shows strong evidence that the use of wearable CGM improves glycemic control (statistically significant HbA1c reduction), reduces hypoglycemia incidents, increases patient adherence, and enhances diabetes-related quality of life. However, challenges such as accuracy under extreme physiological conditions, calibration, sensor lifespan, cost, and patient data interpretation still persist. Promising future prospects include the development of truly non-invasive sensors, enhanced integration with Artificial Intelligence (AI) algorithms for prediction and personalized recommendations, expanded applications for prediabetes and non-diabetic populations, and advancements in miniaturization and biocompatibility. It is concluded that wearable devices for glucose monitoring are revolutionizing diabetes management, offering substantial clinical benefits. Continued research and multidisciplinary collaboration are essential to overcome remaining challenges and realize the full potential of this technology in improving global population health